The influence of salt iodisation on the incidence of thyroid cancer - Karolina P. Sas; Kamila Tokarczyk; Damian Zieliński; Janusz Strzelczyk (Studia Medyczne)
The article analyses the relationship between iodine deficiency, the occurrence of thyroid cancer, and the effectiveness of salt iodisation. Iodine deficiency affects a large number of people around the world, including Poland, where both moderate iodine deficiency and an increase in the incidence of thyroid cancer are observed. The positive effect of salt iodisation on reducing thyroid goitre is noticeable. Additionally, the analysis shows a correlation between the BRAF mutation and an increase in the incidence of papillary cancer, especially in areas with excessive iodine intake. However, it is worth noting that proper iodine intake is associated with a decrease in follicular cancer. The increase in thyroid cancer cases is related to widespread ultrasonography, environmental pollution, diet, as well as recommendations to limit salt intake due to society’s cardiological problems. A constant level of iodine in the body contributes to reducing the malignancy of thyroid cancer, confirming the importance of salt iodisation.